2011
DOI: 10.1111/j.1365-2966.2010.18149.x
|View full text |Cite
|
Sign up to set email alerts
|

UWISH2 - the UKIRT Widefield Infrared Survey for H2

Abstract: We present the goals and preliminary results of an unbiased, near-infrared, narrow-band imaging survey of the first galactic quadrant (10 • < l < 65 • ; −1. • 3 < b < +1. • 3). This area includes most of the giant molecular clouds and massive star forming regions in the Northern hemisphere. The survey is centred on the 1-0 S(1) rovibrational line of H 2 , a proven tracer of hot, dense molecular gas in star-forming regions, around evolved stars, and in supernova remnants. The observations complement existing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 92 publications
1
60
0
Order By: Relevance
“…Our analysis uses data from the UKIRT Widefield Infrared Survey for H2 by Froebrich et al (2011) and its extension towards the Cygnus X and Cassiopeia/Auriga regions discussed in Froebrich et al (2015). All images are taken with the Wide Field Camera (Casali et al 2007) at the UK Infra-Red Telescope.…”
Section: Uwish2 Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis uses data from the UKIRT Widefield Infrared Survey for H2 by Froebrich et al (2011) and its extension towards the Cygnus X and Cassiopeia/Auriga regions discussed in Froebrich et al (2015). All images are taken with the Wide Field Camera (Casali et al 2007) at the UK Infra-Red Telescope.…”
Section: Uwish2 Datamentioning
confidence: 99%
“…by Walawender et al (2005), Hatchell et al (2007), Davis et al (2009) and Khanzadyan et al (2012). In order to establish a truly unbiased sample of jets and outflows from young stars in the Galaxy, not restricted to nearby, mostly low-mass star forming regions, the UKIRT Widefield Infrared Survey for H2 (UWISH2) was conducted by Froebrich et al (2011). In this series of papers we are analysing in detail the identified jets and outflows from young stars in this survey as Molecular Hydrogen emission-line Objects (MHOs) defined in Davis et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we retrieved the UWISH2 image of the H 2 2.12 μm line (Froebrich et al 2011), shown in Fig. 15.…”
Section: Precessing Jetmentioning
confidence: 99%
“…Davis et al (2010) strictly defined molecular hydrogen emissionline objects (MHOs) as the near-infrared manifestations of outflows, and presented a comprehensive catalog of around 1000 MHOs. Deep, wide-field near-infrared imaging with the combination of narrow-band H 2 filter and the corresponding A&A 553, A41 (2013) filter for continuum emission such as a Ks filter has become a very efficient method to detect and identify MHOs (Stanke et al 2002;Khanzadyan et al 2004;Davis et al 2008;Froebrich et al 2011). Morphology, proper motion, as well as association with an HH object or CO outflow, can all provide information concerning the location of the driving source.…”
Section: Introductionmentioning
confidence: 99%